Cost-reduction of waste processing through manufacturing knowledge - Beautru-Frain, Valerie (Cranfield University, 2006)
The rapid transformation of the Waste Management sector has significantly altered the nature of the traditional waste processing business and the nature of competencies required to manage it. With the increase in volume of waste being processed, one element of the transformation of the waste sector, is the move from a craft-industry often with agricultural methods to a post-industrial sector processing high volumes of materials efficiently and effectively. Over the last two centuries the manufacturing sector has also moved from a craft industry to one that learnt how to use technology for material processing, and then learnt how to organise for efficient high-volume production. The application of the coherent techniques developed by various manufacturers (notably Toyota) has resulted in systematic removal of waste (overproduction, waiting, transport etc) and cost in manufacturing. These methods are termed ‘lean manufacturing’. This report describes a project which seeks to test the relevance and value of manufacturing knowledge to waste site operators, by bringing together the expertise and the manufacturing knowledge to waste operators. The industrial aim is to significantly reduce operating costs. It is important to define manufacturing knowledge as that knowledge that specifically relates to lean manufacturing and its implementation. Firstly, the researcher presents an exhaustive and critical literature review of lean manufacturing. Then waste operators’ current practices in operations management are characterised and their existing access to manufacturing knowledge is described, based on interviews with several waste companies. The utility of manufacturing knowledge, and any adjustments needed to suit waste operations will be described, focussing on prioritised areas for improvement and specific proposals for changing operations. The potential scale of these changes can be very important and advantageous when we consider that the Japanese car manufacturer, Toyota, used lean manufacturing to show the then world leading Ford how to reduce production costs by 30%.